Parkinson’s Disease With Depression: The Correlations Between Neuroinflammatory Factors and Neurotransmitters in Cerebrospinal Fluid - Lian, Teng-hong; Guo, Peng; Zhang, Ya-nan; Li, Jing-hui; Li, Li-xia; Ding, Du-yu; Li, Da-ning; Zhang, Wei-jiao; Guan, Hui-ying; Wang, Xiao-min; Zhang, Wei (Frontiers in Aging Neuroscience, 2020)
Background To explore the changes of neuroinflammatory factors in cerebrospinal fluid (CSF) of Parkinson’s disease (PD) with depression (PD-D) patients, and their correlation with monoamine neurotransmitters in PD-D. Methods Neuroinflammatory factors and neurotransmitters in CSF were measured and compared between PD without depression (PD-ND) patients and PD-D patients. The relationship between PD-D and neuroinflammatory factors was studied by binary logistic regression equation, and the related factors of PD-D were adjusted. The correlations of the levels of neuroinflammatory factors and neurotransmitters in PD-D group were analyzed. Results The levels of TNF-α in the CSF of PD-D group were significantly higher and there were no significant differences in the levels of interleukin-1β, prostaglandin E2, hydrogen peroxide and nitric oxide. The 24-item Hamilton Depression Scale (HAMD-24) score was positively correlated with the level of TNF-α in CSF. Binary logistic regression showed that the OR of CSF TNF-α level was 1.035 (95% CI 1.002-1.069). The levels of DA in the CSF of the PD-D group were significantly lower than those in the PD-ND group. TNF-α level were negatively correlated with the DA levels in CSF of PD patients (r=-0.320，P=0.003). Conclusions Neuroinflammatory factors, especially TNF-α, may play an important role in PD-D. It may cause damage to DA neurons and lead to the depletion of DA, which is related to the occurrence and development of PD-D.